A structuralist Kaldor-Thirlwall model of structural change and economic development - Alberto Botta (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
Structuralist models have dealt with the linkages between structural changes and growth for a long time. The issue, however, seems not to have been exhausted, due to the exogenous productive structure framework most structuralist models have adopted so far. The structuralist North-South trade model we present addresses the connection between structural change and development by departing from such a framework. It tries to formalise structural changes and to endogenise the productive structure of backward economies. Its final goal is to analyse how structural changes and industrialization can affect Southern development and its potential for catching up. The framework we assume is heterodox: a binding external constraint to growth is assumed; a modified Verdoon law explains labour productivity dynamics; industrialization is demand-led. Economic development is formalised as a Kaldorian cumulative process between growth and industrialization. Path-dependence and multiple long-run North-South equilibria are the main results. Complex convergence/divergence transitional paths emerge, North-South convergence being conditional to the quality and the intensity of the industrialization process. In this regard, structural changes are necessary but not sufficient conditions for a successful development process. Different institutional settings, as represented by different parametrical settings, have long-lasting effects on growth: the good management by domestic institutions of the ongoing industrialization becomes a complementary requirement. Some concluding parametrical exercises clarify this final point.
Keywords: F12; O14; B50; 330; Structuralist North-South trade models; Economic Development; Structural Change; Kaldorian Cumulative Causation